Kajian Konsentrasi Gula Terhadap Karakteristik Kimia Dan Organoleptik Sirup Daun Kersen (Muntingia calabura L.) - Buton, Sandri; Lawalata, Vita N; Sipahelut, Sophia G (Universitas Pattimura, 2024)
The purpose of this study was to determinan the effect of adding surgar to the chemical and organoleptic properties of cherry leaf syrup. This study was design used was a completely randomized design with I treatment, namely the addition of 75% sugar (A1) 80% sugar addition (A2), the addition of 85% sugar (A3), and the addition of 90% sugar (A4) the treatment was repeated 3 times. The results showed that the concentration of sugar had a very significant affect on the chemical characteristics of total sugar, pH and total solids. %-65.8% while organoleptic for what the researcher prefers color is 2.54 (brown green close to brown), taste 3.0 (sweet), aroma 2.54 (slightly scented with cheey leaves), viscosity 28.87 (thick), and an aftertaste of 1.98 (not better, close to slightly bitter).